Shortcomings of public participation to the decision making process in tourism planning: the case of the Langkawi Islands, Malaysia - Marzuki, Azizan (2008)
Public participation in the decision making process is regarded as an important tool for successful tourism planning. However, in reality, public participation merely at an early stage due to several structural and operational limitations in planning process. A study in Langkawi Islands was conducted to explore and examine approaches used during the preparation of the Langkawi Structure Plan 1990- 2005 and the Langkawi Local Plan 2001-2015. 40 interviews had been conducted with stakeholders in the tourism industry and analysed using ‘framework technique’. Finally, this study found that the limitation of public participation in tourism planning was caused by the weaknesses of the participation approach and the regulation of the Town Planning Act (Act 172) in the Malaysian Planning System. Therefore, it is suggest that an improvement in public participation process in the Langkawi Islands needs to emphasise more towards participation approach and its relationships with the Malaysian Planning System, to ensure that all related issues will be taken into consideration.